The Shakedown of Circular Arches for Movable Loads - Cichoń, C. (Engineering Transactions, 1975)
The static approach is applied to method analysis of arches under movable loads. The shakedown load value cad be computed if the distribution of residual stresses is known, and limits of passive processes are evaluated in discrete numbers of the cross-sections layers. Numerical examples show that the first load passing is decisive and that the range of admitted shakedown loads is limited by value obtained from the first and the second passings.